Digital Ethics and Objectification: A Character and Culturally Based Education Approach to Addressing Online Misconduct Toward Public Figures - Alaiky Uswatul Ulya; Susiati (Jurnal VARIDIKA, 2025)
This study examines digital ethics violations through the sexual objectification of young female celebrities like Billie Eilish, whose culturally significant self-expression in works such as Lunch (2024) and Guess makes her a prime case study for analyzing online misconduct toward public figures. Employing Nussbaum's (1995) objectification framework and qualitative content analysis, the research reveals platform-specific patterns of harassment, with Instagram's visual interface fostering bodily fetishization while X/Twitter facilitates lyric-based vitriol, alongside the weaponization of artistic content for objectification purposes. These findings underscore the failure of current digital etiquette training and highlight the urgent need for character and culturally based education approaches that address online misconduct at its roots. By developing intersectional pedagogical strategies that examine platform architectures, deconstruct cultural narratives enabling public figure objectification, and cultivate critical awareness of digital power dynamics, this study proposes a paradigm shift from reactive moderation to proactive prevention. The research advocates for implementing culturally responsive character education programs incorporating real-world case studies of celebrity harassment, aligning with Sustainable Development Goal 16 while offering practical solutions to transform online spaces through education that tackles both individual behavior and the structural factors perpetuating gendered cyberviolence.